2022
DOI: 10.1002/jnr.25037
|View full text |Cite
|
Sign up to set email alerts
|

Gray matter volume reduction in the emotional brain networks in adults with anosmia

Abstract: Loss of olfaction, or anosmia, frequently accompanies emotional dysfunctions, partly due to the overlapping brain regions between the olfactory and emotional processing centers. Here, we investigated whether anosmia was associated with gray matter volume alterations at a network level, and whether these alterations were related to the olfactory-specific quality of life (QOL) and depressive symptoms. Structural brain magnetic resonance imaging was acquired in 22 individuals with postinfectious or idiopathic ano… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 47 publications
2
7
0
Order By: Relevance
“…That is, middle‐aged to older adults with lower gray matter volume in medial temporal cortex also had lower orbitofrontal gray matter volume. A similar image analysis approach was taken in a study of anosmia in which a pattern of medial temporal gray matter volume was observed, with the gray matter volume within this structural network differing between controls and anosmics 47 . Our results are also partially consistent with evidence that odorant identification, and not detection threshold, was significantly associated with orbitofrontal gray matter volume in older adults with mild cognitive impairment 48 .…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…That is, middle‐aged to older adults with lower gray matter volume in medial temporal cortex also had lower orbitofrontal gray matter volume. A similar image analysis approach was taken in a study of anosmia in which a pattern of medial temporal gray matter volume was observed, with the gray matter volume within this structural network differing between controls and anosmics 47 . Our results are also partially consistent with evidence that odorant identification, and not detection threshold, was significantly associated with orbitofrontal gray matter volume in older adults with mild cognitive impairment 48 .…”
Section: Discussionsupporting
confidence: 83%
“…A similar image analysis approach was taken in a study of anosmia in which a pattern of medial temporal gray matter volume was observed, with the gray matter volume within this structural network differing between controls and anosmics. 47 Our results are also partially consistent with evidence that odorant identification, and not detection threshold, was significantly associated with orbitofrontal gray matter volume in older adults with mild cognitive impairment. 48 Thus, there is replication of medial temporal and orbitofrontal associations with olfactory function across studies when using a similar analysis approach and when considering memory-related declines.…”
Section: Gray Matter Effectssupporting
confidence: 88%
“…In alignment with prior research [ 21 , 23 ], the ICA output was configured to 10 components. Each component was subject to thresholding at z=3.0, preserving only the voxels contributing significantly to the component.…”
Section: Methodsmentioning
confidence: 99%
“…Recognizing that brain regions are interconnected both structurally and functionally, disease-related atrophy often appears within networks of highly correlated regions rather than a single isolated anatomical structure [ 17 , 18 ]. Imaging the networks of brain regions with structural correlations can provide insights into disease-specific pathologies at the network level [ 17 - 24 ]. Moreover, the multivariate network-based analysis employs a model-free approach, negating the need for pre-selected regions [ 22 , 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…Previous neuroimaging studies, including our own [ 8 ], have demonstrated the structural brain alterations associated with anosmia [ 3 , 9 ]. These studies have focused on regions within both the primary olfactory network, such as the olfactory cortex, amygdala, and entorhinal cortex, and the secondary olfactory network, including the orbitofrontal cortex [ 3 , 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%